A tree-based QoS multicast routing protocol for MANETs - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K. (2011)
Multicasting communication serves as one critical operation to support many applications of Mobile Ad hoc networks (MANETs) that achieve group communication rather than pairs of individuals. Multicast routing protocols becomes increasingly important in MANETs because they effectively coordinate a set of nodes. Also, it provides efficient routing for multimedia applications such as video conferences, military and rescue operations. Such applications are highly demand for Quality of Service (QoS), which makes an efficient QoS multicast routing protocols is very important. In this paper, we propose a model that searches for QoS paths from a single source to a set of destinations. The physical area is partitioned into equal size hexagonal cells and a leader and backup leader nodes is elected to maintain up-to-date information about the network topology. Efficient routing is performed based on nodes positions to deliver data packets to all the receivers. The simulation results show that, comparing with the well-known multicast protocol ODMRP (Demand Multicast Routing Protocol), PBQMRP achieves less packet drop ratio with significant reduction in control overhead.